PTU-069 The Effect of Faecal Calprotectin on the use of Colonoscopy at Lancashire Teaching Hospitals NHS Foundation Trust. (4th June 2013) - Shuttleworth, E; Poppleton, A; Lim, E; Sharma, A
Abstract : Introduction: Faecal calprotectin is a sensitive measure of neutrophilic intestinal inflammation; use in gastroenterological screening has been proposed, reducing invasive and costly lower gastrointestinal (GI) endoscopy, particularly when functional disorders are suspected [1]. We reviewed all faecal calprotectin results and available patient records over a six month period to determine whether a normal faecal calprotectin resulted in subsequent avoidance of lower GI endoscopy. Methods: The paper and/or electronic medical records for patients with calprotectin requests over a 6 month period were accessed and reviewed by a Specialty Trainee in gastroenterology at Lancashire Teaching Hospitals NHS Foundation Trust. Demographic data, symptoms, and recent or subsequent lower GI endoscopy were recorded. Endoscopy was considered 'spared' if the diagnosis was anticipated to be functional and a normal faecal calprotectin resulted in avoidance of lower GI endoscopy; or in patients with known inflammatory bowel disease (IBD) where the notes intimated a normal calprotectin would result in avoidance of further endoscopy. Results: 122 patients (73 female, mean age 41yrs, range 16–89yrs) had faecal calprotectin requests sent from the Royal Preston Hospital and Chorley and South Ribble Hospital. 4 samples were not received or processed. 90.2% were outpatient requests, and the most common indications were loose stools (54.1%) and abdominal pain (28.7%). 45 samples (36.9%) had a raised calprotectin (≥51μg/g), of which 20 patients had known IBD. In those with a normal calprotectin (n = 73), 56 had an unclear diagnosis of which 4 (7.1%) eventually went on to have lower GI endoscopy with no major findings, and 20 patients (35.7%) had previously undergone lower GI endoscopy. In 13 patients there were insufficient records available to be able to comment. According to the criteria mentioned 35 patients were spared lower GI endoscopy within the 6 month period. Conclusion: Over a 6 month period 35 lower GI endoscopies were avoided representing both a reduction in patient exposure to the risks of endoscopy and a significant financial saving. Our results suggest that faecal calprotectin is a valuable and cost effective resource in helping to exclude significant organic pathology in selected patients given its proven high negative predictive value in excluding gastrointestinal inflammation [2]. Disclosure of Interest: None Declared References: Licata A et al. J Clin Gastroenterol. 2012; 46:504–8. Meucci G et al. Dig Liver Dis. 2010; 42:191–5